Telegram para el ejercicio de la comunicación interna: análisis de su uso en universidades hispanohablantes - Dr. Rodrigo CISTERNAS-OSORIO,Ddo. Alberto J. LÓPEZ-NAVARRETE,Dra. Margarita CABRERA-MÉNDEZ,Dra. Rebeca DÍEZ-SOMAVILLA (Fonseca, Journal of Communication, 2023)
The digital communication of higher education institutions has acquired great importance in the design of university policies, increasing the digital channels where the institutions have a presence.This study analyzes the digital communication of Spanish-speaking universities through the messaging application Telegram. The official accounts of the most active universities in Ecuador, Colombia, Peru, Chile, and Spain were located and analyzed